PEMAKNAAN MASYARAKAT MUSLIM KABUPATEN PEKALONGAN TENTANG HUKUM WARIS ISLAM - Yusron, Muhammad; Yuliyanti, Tsalisa; Mujadid, Mujadid; Novitasari, Eva (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research discusses the interpretation of the muslim community in Pekalongan Regency regarding Islamic inheritance law. There are two questions that are the focus of discussion in this research, namely about how the interpretation of the muslim community of Pekalongan Regency about Islamic inheritance law, and how the implications of the interpretation of the Muslim community of Pekalongan Regency regarding Islamic inheritance law on the practice of inheritance distribution. This research is legal sociology research. The technical analysis used is qualitative descriptive analysis, to describe and explain data in the form of the interpretation of the muslim community about Islamic inheritance law that has been obtained as it is. The research concluded that: First, the understanding of muslim community in Pekalongan Regency about Islamic inheritance law was not significantly correlated with the level of formal education. Second, one's level of understanding of Islamic inheritance law does not necessarily coincide with the level of interpretation of the law. Interpretation better reflects how the understanding is applied in daily practice. Interpretation can be influenced by social, cultural, economic, and individual or family context factors. Third, the interpretation of Islamic inheritance law has implications for the practice of implementing the distribution of inheritance.